Message in a bottle – The story of floating plastic in the eastern Mediterranean sea. (July 2018) - Pasternak, Galia; Zviely, Dov; Ariel, Asaf; Spanier, Ehud; Ribic, Christine A.
Abstract: The Mediterranean Sea is a closed basin with limited water exchange through the Strait of Gibraltar, and sites along its shores show the greatest densities of marine debris in the world. Plastic bottles, which are a growing concern due to high consumption of soft drinks and bottled water, constitute most of the floating marine debris. In this paper we present the transport mechanisms of floating marine debris to and from the Israeli coast using an experimental offshore release and recovery of plastic bottles, with the participation of citizens. Many bottles released near the beach in the south part of Israel, returned to the beach at a short distance and time from the release point. Some release locations had no bottle returns. Ten bottles, released from three locations, were recovered many dozens to hundreds of kilometers from the release point. Since most of the westward water flow in the eastern Mediterranean is subsurface, it was not surprising to find our floating debris only in the east. That makes the Levant basin in the eastern Mediterranean a collection area for floating debris.